W poszukiwaniu drogi do emancypacji – godność osoby starszej i ageizm w świetle koncepcji praw człowieka oraz w perspektywie rozwoju współczesnego społeczeństwa - Szczupał, Bernadeta; Chatzipentidis, Kiriakos (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2016)
In this article we will present selected issues on the international protection of the dignity of the elderly and dignity as a human right in the internal legal order. We will also present danger to dignity of older persons in the contemporary social reality. We will show the complexity of the problems, expectations, and challenges faced by the elderly. We’ll discuss situations that threaten their sense of dignity, as well as a conscious way of the elderly leading to the realization of this feeling, and we will draw attention to the prohibition of discrimination based on age in the general international law.